2017
DOI: 10.1038/nrdp.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes mellitus

Abstract: Type 1 diabetes mellitus (T1DM), also known as autoimmune diabetes, is a chronic disease characterized by insulin deficiency due to pancreatic β-cell loss and leads to hyperglycaemia. Although the age of symptomatic onset is usually during childhood or adolescence, symptoms can sometimes develop much later. Although the aetiology of T1DM is not completely understood, the pathogenesis of the disease is thought to involve T cell-mediated destruction of β-cells. Islet-targeting autoantibodies that target insulin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
709
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 955 publications
(843 citation statements)
references
References 225 publications
4
709
0
16
Order By: Relevance
“…Type 2 diabetes–the predominant subtype of diabetes—mostly develops in adulthood 1112. In contrast, type 1 diabetes usually develops in childhood and is considered rare among adults 111314. Although previous studies in the United States151617 and elsewhere18 have reported the prevalence of diabetes among adults on the basis of national health surveys,151617 little is known about the prevalence by diabetes subtypes (eg, type 1 and type 2 diabetes) in adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 2 diabetes–the predominant subtype of diabetes—mostly develops in adulthood 1112. In contrast, type 1 diabetes usually develops in childhood and is considered rare among adults 111314. Although previous studies in the United States151617 and elsewhere18 have reported the prevalence of diabetes among adults on the basis of national health surveys,151617 little is known about the prevalence by diabetes subtypes (eg, type 1 and type 2 diabetes) in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuing improvement in treatment of type 1 diabetes,1113 more children with this form of diabetes are expected to survive to adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, type 2 diabetes is characterized by hyperglycemia and insulin resistance, often in the setting of overweight and obesity [54, 55], while type 1 diabetes is distinguished by autoimmune destruction of the pancreatic β-cells with resultant insulin deficiency requiring lifelong insulin treatment [56]. …”
Section: Diabetesmentioning
confidence: 99%
“…K8 +/− mouse blood glucose levels were also higher than in K8 +/+ mice after STZ treatment at the two‐week time point (Figure 3B) and remained at a higher level in K8 +/− mice until the end of the experiment (not shown). Moreover, polyuria, which is an indication of the severity of diabetes,25 was significantly increased in STZ‐treated diabetic K8 +/− compared with K8 +/+ mice at 34 days post‐STZ treatments (Figure 3c), confirming the more severe diabetic condition in these mice. In untreated control mice, no differences in urine volume were seen between the genotypes (Figure 3C).…”
Section: Resultsmentioning
confidence: 61%